⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ a + b + c + d a 2 + b 2 + c 2 + d 2 a 3 + b 3 + c 3 + d 3 a 4 + b 4 + c 4 + d 4 = 2 = 4 = 5 = 8
Given the above, find a 2 5 + b 2 5 + c 2 5 + d 2 5 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Newton Sums, nice!
Rockin' great solution, Chew-Seong!
From @Chew-Seong Cheong 's solution, we can also know that S 1 = 2 , S 2 = 0 , S 3 = − 1 , S 4 = 0 , so a , b , c , d are the roots of the equation x 4 − 2 x 3 + x = 0 and the roots are 0 , 1 , ϕ , 1 − ϕ . Substitute them in and we get our answer.
Problem Loading...
Note Loading...
Set Loading...
The problem can be solved using Newton's sums . Let P n = a n + b n + c n + d n , where n is an positive integer, S 1 = a + b + c + d = 2 , S 2 = a b + a c + a d + b c + b d + c d , S 3 = a b c + a b d + a c d + b c d , and S 4 = a b c d . Then
P 1 P 2 P 3 P 4 P n = S 1 = 2 = S 1 P 1 − 2 S 2 = 4 − 2 S 2 = 4 = S 1 P 2 − S 2 P 1 + 3 S 3 = 8 − 0 + 3 S 3 = 5 = S 1 P 3 − S 2 P 2 + S 3 P 1 − 4 S 4 = 1 0 − 0 − 2 − 4 S 4 = 8 = S 1 P n − 1 − S 2 P n − 2 + S 3 P n − 3 − S 4 P n − 4 = 2 P n − 1 − P n − 3 ⟹ S 1 = 2 ⟹ S 2 = 0 ⟹ S 3 = − 1 ⟹ S 4 = 0
We can use the linear recurrence relation P n = 2 P n − 1 − P n − 3 to solve progressively from P 5 to P 2 5 . Alternatively, we solve the linear recurrence relation and we get P n = φ n + ( 1 − φ ) 2 + 1 , where φ = 2 1 + 5 is the golden ratio (see note). Then P 2 5 = φ 2 5 + ( 1 − φ ) 2 5 + 1 = 1 6 7 7 6 2 .
Note: The characteristic equation of P n = 2 P n − 1 − P n − 3 is:
r 3 r 3 − r 2 − 1 ( r − 1 ) ( r 2 − r − 1 ) ⟹ r ⟹ P n = 2 r 2 − 1 = 0 = 0 = 1 , φ , 1 − φ = c 1 + c 2 φ n + c 3 ( 1 − φ ) n
P 1 : P 2 : P 3 : P 2 − P 1 : P 3 − P 2 : c 1 + c 2 φ + c 3 ( 1 − φ ) = 2 c 1 + c 2 φ 2 + c 3 ( 1 − φ ) 2 = c 1 + c 2 ( 1 + φ ) + c 3 ( 2 − φ ) = 4 c 1 + c 2 φ 3 + c 3 ( 1 − φ ) 3 = c 1 + c 2 ( 1 + 2 φ ) + c 3 ( 3 − 2 φ ) = 5 c 2 + c 3 = 2 c 2 φ + c 3 ( 1 − φ ) = 1
( 1 − φ ) ( P 2 − P 1 ) − ( P 3 − P 2 ) : P 2 − P 1 : P 1 : c 2 ( 1 − 2 φ ) = 1 − 2 φ 1 + c 3 = 2 c 1 + φ + 1 − φ = 2 ⟹ c 2 = 1 ⟹ c 3 = 1 ⟹ c 1 = 1